الآثار الفقهية والنفسية لغياب أحد الزوجين على الحقوق الزوجية: دراسة تحليلية / The jurisprudential and psychological effects of the absence of one of the spouses on marital rights: an analytical study - Hasin, Abdul Wasi; Zaroum, AbdulHamid Mohamed Ali (Al Hikmah Research and Publication Centre, 2022)
يتناول المقال قضية مهمة تتمثل في غياب الزوجين بسبب السفر والآثار الفقهية والنفسية التي تنجم عن ذلك من حيث التفريط في حقوق الزوجية وحقوق أولادهما. استخدم البحث المنهج الاستقرائي من أجل تتبع الجزئيات العلمية من نصوص الشّريعة المطهّرة وآراء الفقهاء، كما تم توظيف المنهج التحليلي لتحليل الآراء والأقوال والبحوث العلمية المتعلقة بالموضوع. توصلت الدراسة إلى جملة من النتائج، أهمها: أنه تترتب على عقد النكاح الصحيح آثار الزواج، من الحقوق الخاصة بالزوج، والحقوق الخاصة بالزوجة، والحقوق المشتركة بينهما، وحقوق أبنائهما، والاعتناء بالمقاصد الأصلية والفرعية للزواج من: إعفاف النفس ومجاهدتها، وحفظ الأنساب، وتربية الأولاد، والإبقاء على النوع الإنساني، وإيجاد الأسرة المتماسكة السعيدة، وتحصين الزوجين، وصيانة المرأة وحفظها من الامتهان والمذلة، وغير ذلك. وأن الفقهاء اجتهدوا في استنباط أساليب شرعية للغياب الطويل وأسبابه المؤثرة ماديًا كانت أو معنويا، وأن ابتعاد أحد الزوجين سبب مؤثر على بعض الحقوق الهامة للأبناء، من: النفقة، والحضانة، والمراقبة، والتربية، والتعليم. وخَلُصَ البحث إلى جملة من التوصيات، أهمّها: الاعتناء بالجوانب النفسية لكلا الزوجين وللأطفال، وضرورة مراعاة مقاصد الزواج الأصلية والتبعية، ومحاولة قصارى الجهد في أداء الحقوق المادية أو المعنوية أو الاجتماعية أو الاقتصادية، والسكن في مسكن واحد ورعاية الأسرة بشكل خاص، والاجتهاد قدر الإمكان في عدم الغياب الطويل، والالتزام بضوابط الشريعة المهمة في تشكيل الحياة الإسلامية. / The article deals with an important issue concerning familial relations, the jurisprudential and psychological effects of the absence of one of the spouses on marital rights. This analytical study attempts to investigate this problem that results from such an absence in terms of neglecting marital rights and the rights of their children. The research used the inductive method in order to track the scientific particles from the texts of the Sharia and the opinions of the jurists, and the analytical method was used to analyze the opinions, sayings and scientific research related to the subject. The study reached a number of results, the most important of which are: that the correct and valid marriage contract entails the effects of marriage, from the rights of the husband, the rights of the wife, the common rights between them, and the rights of their children, as well as taking care of the main and the subsidiary purposes of marriage. Among these purposes, self-chastity and struggle, preserving lineages, raising children Preserving the human kind, creating a cohesive and happy family, protecting the spouses, preserving women and protecting them from abuse and humiliation, and some others. Muslim jurists strived to devise legal methods for spouses’ long absence and its influential reasons, whether material or moral, and that the absence of one of the spouses is a reason affecting some of the important rights of children, such as: aliment or outlay, custody, supervision, upbringing, and education. The research concluded with a number of recommendations, the most important of which are: taking care of the psychological aspects of both spouses and children, the need to take into account the main and the subsidiary purposes of marriage, trying every effort to fulfill the material, moral, social or economic rights, living together in one house and caring for the family in particular, and striving as much as possible not to be absent for a long period of time, and to adhere to the important Sharia rules in shaping the Islamic life.